수용액 분사법에 의한 용융아연 도금강판의 미니스팡글 형성 - 김종상(J. S. Kim); 전선호(S. H. Jeon); 박정렬(J. R Park) (Biuletyn Uniejowski, 1994)
The formation of spangles on a hot dip galvanized sheet steel by spray cooling the molten zinc coating with air, water and 2.0wt% $NH_4H_2PO_4$ solution has been studied performing laboratory experiments, and their coating properties have been evaluated. Minimized spangles were easily formed by mist spraying the solution for 1 second at the low nozzle spray pressure onto the molten zinc at 420~$422^{°}C$ because the solute $NH_4H_2PO_4$ in the sprayed solution imparted a highly rapid cooling effect to the coating through its endothermic de-composition reactions and because the decomposed products acted as numerous nucleation sites for the mini-mized spangles on the coating. Good surface appearances sand sound coating properties were obtained on this coating. Only regular spangles were formed on the coating by the forced convective air cooling. At the high nozzle spray pressure, zero spangles were formed on the coating by the pure water spray cooling. However, the coating had a dull and rough surface with craters sand cracks.